Experimental substantiation of kidney sutures - S. V. Shkodkin; Yu. B. Idashkin; M. Z. A. A. Zubaidi; A. D. Kravets; A. F. Khuseinzoda; Zh. K. Askari; E. G. Ponomarev; V. Y. Nechiporenko; K. S. Shkodkin (Вестник урологии, 2022)
Introduction. Partial nephrectomy occupies a rightful priority position in the treatment of localized renal cell carcinoma. It not only provides high oncological results but also allows you to save the renal parenchyma. This reduces the risk of chronic kidney disease and cardiovascular accidents, which is especially important in young patients. The main technical problem is the closure of the renal wound with reliable hemostasis and low risk of urine leakage, especially in patients with large endophytic lesions.Objective. To study the mechanical properties of the renal parenchyma and to establish ways to prevent suture eruption under an experimental model.Materials and methods. The studies were carried out using the equipment of the Center for Collective Use "Technologies and Materials of the Belgorod State National Research University". Mechanical tests of the strength characteristics of the layers of the renal parenchyma were performed on 60 cadaveric kidneys. The tensile strength and tension of tissues during the application of various surgical sutures, as well as variants of the latter with the use of spacers made of materials that prevent thread eruption, were studied using a tensile machine.Results. During mechanical tests, the medulla was found to have the highest strength (23.58 ± 9.17 load (L)) between the layers of the renal parenchyma. The mechanical strength (8.40 ± 2.89 L) of the cortical substance in the absence of the capsule was minimal. When replacing the vertical suture through all layers by tied a knot along the resection line with a similar horizontal mattress suture, it significantly increased tensile strength (27.35 ± 12.04 L) to levels comparable to the tensile strength of the medulla. The use of a hemostatic mesh (SurgicelÒ) as a lining did not significantly affect the ultimate strength (23.58 ± 9.17 L) of the horizontal mattress suture. The use of a prolene mesh (LintexÒ mesh) for this purpose significantly prevented suture eruption (31.48 ± 9.98 L) compared to the native suture and the SurgicelÒ mesh. The maximum tensile strength (45.61 ± 6.1 L) of a horizontal mattress suture was obtained for a tape made of a polytetrafluoroethylene vascular prosthesis.Conclusion. The study of the mechanical strength of the layers of the renal parenchyma showed the inexpediency of performing a cortical suture. The use of a horizontal mattress suture significantly increases the tensile strength compared to a vertical one. Maximum mechanical strength characteristics were obtained using polytetrafluoroethylene inserts.